Birth Cohort Effects in Breast Cancer Incidence: Global Patterns and Trends. Issue 12 (1st July 2022) - Chen, Yi-Chu; Lien, Wan-Ching; Su, Shih-Yung; Jhuang, Jing-Rong; Chiang, Chun-Ju; Yang, Ya-Wen; Lee, Wen-Chung
Abstract: Breast cancer is the most common neoplasm in the world among women. The age-specific incidences and onset ages vary widely between Asian and Western countries/regions. Invasive breast cancer cases among women from 1997 to 2011 were abstracted from the International Agency for Research on Cancer and the Taiwan Cancer Registry. Age-period-cohort analysis was performed to examine the trends. The cohort effect was prominent in South Korea, Taiwan, Japan, and Thailand, possibly related to the timing of westernization. The risk of breast cancer initially rose with the birth cohorts in Hong Kong and India (both former British colonies), peaked, and then declined in recent birth cohorts. Unlike other Asian countries/regions, virtually no birth cohort effect was identified in the Philippines (a Spanish colony in 1565 and the first Asian country to adopt Western cultural aspects). Moreover, an at-most negligible birth cohort effect was identified for all ethnic groups (including Asian immigrants) in the United States. This global study identified birth cohort effects in most Asian countries/regions but virtually no impact in Western countries/regions. The timing of westernization was associated with the birth cohort effect.